Audrey L.

asked • 12/17/20

Prove that the following argument is valid in QL: ∃x[~Bxm& ∀y(Cy → ~Gxy)], ∀z[~∀y(Wy →Gzy) → Bzm], ∴∀x(Cx → ~Wx)

General ways to approach and how to start would be greatly appreciated.

1 Expert Answer


Still looking for help? Get the right answer, fast.

Ask a question for free

Get a free answer to a quick problem.
Most questions answered within 4 hours.


Find an Online Tutor Now

Choose an expert and meet online. No packages or subscriptions, pay only for the time you need.